Detecting and developing new business opportunities in society 5.0 contexts: A sociotechnical approach - Çipi, A.; Fernandes, A.; Ferreira, F.; Ferreira, N.; Meidute-Kavaliauskiene, I. (Technology in Society, 2023)
Rapid technological evolution has become a great challenge for businesses and societies due to the openness provided by new digital technologies, platforms, and infrastructure and to the impacts of these innovations on how people work and live. The concept of a super-smart society (i.e., Society 5.0) comprises a fresh way to apply these innovations, in which human beings contribute to adapting technologies to daily activities in their society and making Society 5.0 ideas applicable to different areas of each individual’s life. Digital transformation and technological innovation are basic components of this paradigm. This study sought to develop a decision-support model that can help companies structure and prioritize new business opportunities within Society 5.0 contexts. The analysis system relies on a constructivist approach that promotes debates between specialists and combinations of methodologies such as cognitive mapping and interpretive structural modeling. The results highlight the most important areas in which new business opportunities can arise, thereby demonstrating that the proposed model is a valuable tool for incorporating a future orientation into business technological innovation initiatives.